Results for: z-rich-2

How is newest proof Fermat?

Pierre De Fermat 's last Theorem.The conditions:x,y,z,n are the integers and >0. n>2.Proof:z^n=/x^n+y^n.We have;z^3=[z(z+1)/2]^2-[(z-1)z/2]^2Example;5^3=[5(5+1)/2]^2-[5(5-1)/2]^2=225-100=125Andz^3+(z-1)^3=[z(z+1)/2]^2-[(z-2)(z-1)/2]^2Example;5^3+4^3=[5(5+1)/2]^2-[(5-2)(5-1)/2]^2=225-36=189Andz^3+(z-1)^3+(z-2)^3=[z(z+1)/2]^2-[(z-3)(z-2)/2]^2Example5^3+4^3+2^3=[5(5+1)/2]^2-[(5-3)(5-2)/2]^2=225-9=216Andz^3+(z-1)^3+(z-2)^3+(z-3)^3=[z(z+1)/2]^2-[(z-4)(z-3)/2]^2Example5^3+4^3+3^3+2^3=[5(5+1)/2]^2-[(5-4)(5-3)/2]^2=225-1=224General:z^3+(z-1)^3+....+(z-m)^3=[z(z+1)/2]^2-[(z-m-1)(z-m)/2]^2We have;z^3=z^3+(z-m-1)^3 - (z-m-1)^3.Because:z^3+(z-m-1)^3=[z^3+(z-1)^3+....+(z-m-1)^3] - [(z-1)^3+....+(z-m)^3]Soz^3=[z(z+1)/2]^2-[(z-m-2)(z-m-1)/2]^2 - [z(z-1)/2]^3+[(z-m-1)(z-m)/2]^2 - (z-m-1)^3.Similar:z^3=z^3+(z-m-2)^3 - (z-m-2)^3.Soz^3=[z(z+1)/2]^2-[(z-m-3)(z-m-2)/2]^2 - [z(z-1)/2]^3+[(z-m-2)(z-m-1)/2]^2 - (z-m-2)^3.........Suppose:z^n=x^n+y^nSoz^(n-3)*z^3=x^(n-3)^n*x^3+y^(n-3)*y^3.Soz^(n-3)*{[z(z+1)/2]^2-[(z-m-2)(z-m-1)/2]^2 - [z(z-1)/2]^3+[(z-m-1)(z-m)/2]^2 - (z-m-1)^3}=x^(n-3)*{[x(x+1)/2]^2-[(x-m-2)(x-m-1)/2]^2 - [x(x-1)/2]^3+[(x-m-1)(x-m)/2]^2 - (x-m-1)^3}+y^(n-3)*{[y(y+1)/2]^2-[(y-m-2)(y-m-1)/2]^2 - [y(y-1)/2]^3+[(y-m-1)(y-m)/2]^2… Full Answer

Can you understand my proof about Fermat?

Pierre De Fermat 's last Theorem.The conditions:x,y,z,n are the integers and >0. n>2.Proof:z^n=/x^n+y^n.We have;z^3=[z(z+1)/2]^2-[(z-1)z/2]^2Example;5^3=[5(5+1)/2]^2-[5(5-1)/2]^2=225-100=125Andz^3+(z-1)^3=[z(z+1)/2]^2-[(z-2)(z-1)/2]^2Example;5^3+4^3=[5(5+1)/2]^2-[(5-2)(5-1)/2]^2=225-36=189Andz^3+(z-1)^3+(z-2)^3=[z(z+1)/2]^2-[(z-3)(z-2)/2]^2Example5^3+4^3+2^3=[5(5+1)/2]^2-[(5-3)(5-2)/2]^2=225-9=216Andz^3+(z-1)^3+(z-2)^3+(z-3)^3=[z(z+1)/2]^2-[(z-4)(z-3)/2]^2Example5^3+4^3+3^3+2^3=[5(5+1)/2]^2-[(5-4)(5-3)/2]^2=225-1=224General:z^3+(z-1)^3+....+(z-m)^3=[z(z+1)/2]^2-[(z-m-1)(z-m)/2]^2We have;z^3=z^3+(z-m-1)^3 - (z-m-1)^3.Because:z^3+(z-m-1)^3=[z^3+(z-1)^3+....+(z-m-1)^3] - [(z-1)^3+....+(z-m)^3]Soz^3=[z(z+1)/2]^2-[(z-m-2)(z-m-1)/2]^2 - [z(z-1)/2]^3+[(z-m-1)(z-m)/2]^2 - (z-m-1)^3.Similar:z^3=z^3+(z-m-2)^3 - (z-m-2)^3.Soz^3=[z(z+1)/2]^2-[(z-m-3)(z-m-2)/2]^2 - [z(z-1)/2]^3+[(z-m-2)(z-m-1)/2]^2 - (z-m-2)^3.........Suppose:z^n=x^n+y^nSoz^(n-3)*z^3=x^(n-3)^n*x^3+y^(n-3)*y^3.Soz^(n-3)*{[z(z+1)/2]^2-[(z-m-2)(z-m-1)/2]^2 - [z(z-1)/2]^3+[(z-m-1)(z-m)/2]^2 - (z-m-1)^3}=x^(n-3)*{[x(x+1)/2]^2-[(x-m-2)(x-m-1)/2]^2 - [x(x-1)/2]^3+[(x-m-1)(x-m)/2]^2 - (x-m-1)^3}+y^(n-3)*{[y(y+1)/2]^2-[(y-m-2)(y-m-1)/2]^2 - [y(y-1)/2]^3+[(y-m-1)(y-m)/2]^2… Full Answer

What are the efforts of Africa to solve the global news flow disequilibrium?

Pierre De Fermat 's last Theorem.The conditions:x,y,z,n are the integers and >0. n>2.Proof:z^n=/x^n+y^n.We have;z^3=[z(z+1)/2]^2-[(z-1)z/2]^2Example;5^3=[5(5+1)/2]^2-[5(5-1)/2]^2=225-100=125Andz^3+(z-1)^3=[z(z+1)/2]^2-[(z-2)(z-1)/2]^2Example;5^3+4^3=[5(5+1)/2]^2-[(5-2)(5-1)/2]^2=225-36=189Andz^3+(z-1)^3+(z-2)^3=[z(z+1)/2]^2-[(z-3)(z-2)/2]^2Example5^3+4^3+2^3=[5(5+1)/2]^2-[(5-3)(5-2)/2]^2=225-9=216Andz^3+(z-1)^3+(z-2)^3+(z-3)^3=[z(z+1)/2]^2-[(z-4)(z-3)/2]^2Example5^3+4^3+3^3+2^3=[5(5+1)/2]^2-[(5-4)(5-3)/2]^2=225-1=224General:z^3+(z-1)^3+....+(z-m)^3=[z(z+1)/2]^2-[(z-m-1)(z-m)/2]^2We have;z^3=z^3+(z-m-1)^3 - (z-m-1)^3.Because:z^3+(z-m-1)^3=[z^3+(z-1)^3+....+(z-m-1)^3] - [(z-1)^3+....+(z-m)^3]Soz^3=[z(z+1)/2]^2-[(z-m-2)(z-m-1)/2]^2 - [z(z-1)/2]^3+[(z-m-1)(z-m)/2]^2 - (z-m-1)^3.Similar:z^3=z^3+(z-m-2)^3 - (z-m-2)^3.Soz^3=[z(z+1)/2]^2-[(z-m-3)(z-m-2)/2]^2 - [z(z-1)/2]^3+[(z-m-2)(z-m-1)/2]^2 - (z-m-2)^3.........Suppose:z^n=x^n+y^nSoz^(n-3)*z^3=x^(n-3)^n*x^3+y^(n-3)*y^3.Soz^(n-3)*{[z(z+1)/2]^2-[(z-m-2)(z-m-1)/2]^2 - [z(z-1)/2]^3+[(z-m-1)(z-m)/2]^2 - (z-m-1)^3}=x^(n-3)*{[x(x+1)/2]^2-[(x-m-2)(x-m-1)/2]^2 - [x(x-1)/2]^3+[(x-m-1)(x-m)/2]^2 - (x-m-1)^3}+y^(n-3)*{[y(y+1)/2]^2-[(y-m-2)(y-m-1)/2]^2 - [y(y-1)/2]^3+[(y-m-1)(y-m)/2]^2… Full Answer

Is your proof about Fermat true or false?

PIERRE DE FERMAT' S LAST THEOREM. CASE SPECIAL N=3 AND.GENERAL CASE N>2. . THE CONDITIONS.Z,X,Y,N ARE THE INTEGERS . Z*X*Y*N>0.N>2. Z^3=/=X^3+Y^3 AND Z^N=/=X^N+Y^N. SPECIAL CASE N=3. WE HAVE (X^2+Y^2)^2=X^4+Y^4+2X^2*Y^2. BECAUSE X*Y>0=>2X^2*Y^2>0. SO (X^2+Y^2)^2=/=X^4+Y^4. CASE 1. IF Z^2=X^2+Y^2 SO (Z^2)^2=(X^2+Y^2)^2 BECAUSE… Full Answer

Who do solve Fermat 's last Theorem?

PIERRE DE FERMAT' S LAST THEOREM. CASE SPECIAL N=3 . THE CONDITIONS.Z,X,Y,N ARE THE INTEGERS . Z*X*Y*N>0.N>2. Z^3=/=X^3+Y^3 WE HAVE (X^2+Y^2)^2=X^4+Y^4+2X^2*Y^2. BECAUSE X*Y>0=>2X^2*Y^2>0. SO (X^2+Y^2)^2=/=X^4+Y^4. CASE 1. IF Z^2=X^2+Y^2 SO (Z^2)^2=(X^2+Y^2)^2 BECAUSE (X^+Y^2)^2=/=X^4+Y^4. SO (Z^2)^2=/=X^4+Y^4. SO Z^4=/=X^4+Y^4. CASE 2. IF… Full Answer